Global Pandemic as an Innovative Impulse for the Labour Market - Linkeschová, Dana; Tichá, Alena; Nový, Martin; Tichý, Jan (SHS Web of Conferences, 2021)
Research background: The global history of mankind in an international context is permeated by the painful events include epidemics, wars, natural disasters and crises, including economic ones. Purpose of the article: According to research, it will be the generation of hatcheries from digital talents. In the work environment, however, centennials behave differently than all previous generations. Millenials is a fully technological generation with great self-confidence, but at the same time an autonomous willingness to work hard, assertive and much more demanding operating with completely different and international communication tools. Methods: The article will analyses the surveys of international research about the international crisis caused by the pandemic by methods of mathematical statistics. It has paradoxically accelerated digitization in fields where it has been difficult to assert itself so far. Findings & Value added:.Along with the changing behavior of the next generation and the advancing digitization and automation of work, many professions are at risk. The article deals with the possible development of the labor market in connection with the complete disappearance of some professions, but also the emergence of new professions, which now cannot even be imagined. Several weeks of quarantine, caused by a pandemic of a new type of coronavirus, has changed the lives of many companies and employees. For some companies, it meant their definitive end. For others, however, it foreshadowed the acceleration of innovation in the company itself.

Research background: The global history of mankind in an international context is permeated by the painful events include epidemics, wars, natural disasters and crises, including economic ones. Purpose of the article: According to research, it will be the generation of hatcheries from digital talents. In the work environment, however, centennials behave differently than all previous generations. Millenials is a fully technological generation with great self-confidence, but at the same time an autonomous willingness to work hard, assertive and much more demanding operating with completely different and international communication tools. Methods: The article will analyses the surveys of international research about the international crisis caused by the pandemic by methods of mathematical statistics. It has paradoxically accelerated digitization in fields where it has been difficult to assert itself so far. Findings & Value added:.Along with the changing behavior of the next generation and the advancing digitization and automation of work, many professions are at risk. The article deals with the possible development of the labor market in connection with the complete disappearance of some professions, but also the emergence of new professions, which now cannot even be imagined. Several weeks of quarantine, caused by a pandemic of a new type of coronavirus, has changed the lives of many companies and employees. For some companies, it meant their definitive end. For others, however, it foreshadowed the acceleration of innovation in the company itself.
Global Pandemic as an Innovative Impulse for the Labour Market
Keywords: Global pandemics; innovation; labour market; competencies; mathematical and quantitative methods; Global pandemics; innovation; labour market; competencies; mathematical and quantitative methods